Nitrogen Fertilizer Suppresses Mineralization of Soil Organic Matter in Maize Agroecosystems - Mahal, Navreet K.; Osterholz, William R.; Miguez, Fernando E.; Poffenbarger, Hanna J.; Sawyer, John E.; Olk, Daniel C.; Archontoulis, Sotirios V.; Castellano, Michael J. (Frontiers in Ecology and Evolution, 2019)
The possibility that N fertilizer increases soil organic matter (SOM) mineralization and, as a result, reduces SOM stocks has led to a great debate about the long-term sustainability of maize-based agroecosystems as well as the best method to estimate fertilizer N use efficiency (FNUE). Much of this debate is because synthetic N fertilizer can positively or negatively affect SOM mineralization via several direct and indirect pathways. Here, we test a series of hypotheses to determine the direction, magnitude, and mechanism of N fertilizer effect on SOM mineralization and discuss the implications for methods to estimate FNUE. We measured the effect of synthetic N fertilizer on SOM mineralization via gross ammonification at two long-term experiments in central and southern Iowa, USA with replicated plots of continuous maize that received one of three ‘historical’ N fertilizer rates (zero, moderate or high) from 1999-2014. In 2015, prior to our measurements, we split the historical N fertilizer rate plots into two subplots that received either the site-specific agronomic optimum N rate or zero N fertilizer. At the onset of rapid maize N uptake, N fertilizer reduced gross ammonification by 13-21% (2-5 kg NH4-N ha-1 d-1). A companion laboratory experiment rejected the hypothesis that differences in net primary productivity between fertilized and unfertilized treatments explained the negative effect of N fertilizer on SOM mineralization. Moreover, the NH4+ pool size was negatively correlated with the gross ammonification rate (r2 = 0.85, p < 0.001). Thus, we conclude that NH4+-N fertilizer had a direct suppressive effect on SOM mineralization. These results demonstrate that the direct effect of N fertilizer on microbial activity can exceed the indirect effects of N fertilizer via large changes in NPP that alter organic matter inputs, soil temperature and moisture content. The magnitude of this effect and specificity to NH4+-N has significant implications for fertilizer management as well as the measurement and modeling of agroecosystem N dynamics including FNUE.